Functional Diversification of Oyster Big Defensins Generates Antimicrobial Specificity and Synergy against Members of the Microbiota - de San Nicolas, Noémie; Asokan, Aromal; Rosa, Rafael, D; Voisin, Sébastien, N; Travers, Marie-Agnès; Rocha, Gustavo; Dantan, Luc; Dorant, Yann; Mitta, Guillaume; Petton, Bruno; Charrière, Guillaume, M; Escoubas, Jean-Michel; et al. (Marine Drugs, 2022)
International audience Big defensins are two-domain antimicrobial peptides (AMPs) that have highly diversified in mollusks. Cg-BigDefs are expressed by immune cells in the oyster Crassostrea gigas, and their expression is dampened during the Pacific Oyster Mortality Syndrome (POMS), which evolves toward fatal bacteremia. We evaluated whether Cg-BigDefs contribute to the control of oyster-associated microbial communities. Two Cg-BigDefs that are representative of molecular diversity within the peptide family, namely Cg-BigDef1 and Cg-BigDef5, were characterized by gene cloning and synthesized by solid-phase peptide synthesis and native chemical ligation. Synthetic peptides were tested for antibacterial activity against a collection of culturable bacteria belonging to the oyster microbiota, characterized by 16S sequencing and MALDI Biotyping. We first tested the potential of Cg-BigDefs to control the oyster microbiota by injecting synthetic Cg-BigDef1 into oyster tissues and analyzing microbiota dynamics over 24 h by 16S metabarcoding. Cg-BigDef1 induced a significant shift in oyster microbiota β-diversity after 6 h and 24 h, prompting us to investigate antimicrobial activities in vitro against members of the oyster microbiota. Both Cg-BigDef1 and Cg-BigDef5 were active at a high salt concentration (400 mM NaCl) and showed broad spectra of activity against bacteria associated with C. gigas pathologies. Antimicrobial specificity was observed for both molecules at an intra- and inter-genera level. Remarkably, antimicrobial spectra of Cg-BigDef1 and Cg-BigDef5 were complementary, and peptides acted synergistically. Overall, we found that primary sequence diversification of Cg-BigDefs has generated specificity and synergy and extended the spectrum of activity of this peptide family.